Respuestas

2012-07-17T01:54:13+02:00

193...

 

a) P(x)=x³-2x²+5x-1      en  x=-1

-Sólo se reemplaza " -01" en "x":

    P(-1)=(-1)³-2(-1)²+5(-1)-1

           = -1-2(1)-5-1

           = -1-2-5-1

    P(-1)= -9

 

b) P(x)=x^5-7          en  x=2

    P(2)= (2)^5 -7

          = 32 -7

    P(2)= 25 

 

c) P(x)= -6x²+3x+2    en x=0

    P(0)= -6(0)²+3(0)+2

          =   0+0+2

    P(0)= 2

 

194...

 

a) x²y-3z³       x=1; y=0; z=-1.

   (1)²(0)-3(-1)³

     1(0)-3(-1)

        0+3

       = 3 

b) 1a²b+1       a=1; b=2

   1(1)²(2)+1

   1(1)(2)+1

          2+1

         = 3

 

c) y²+3yz      y=-1; z=2

   (-1)²+3(-1)(2)

      1 -6

      = -5

 

*Espero haberte ayudado, saludos.